Review of slip-related incidents associated with swimming pools in Spain, 2000-2015 - Gámez de la Hoz, J.; Padilla-Fortes, A.; Padilla-Ruiz, M. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2019)
Swimming pools are a common source of slip-induced falls, with a high socioeconomic cost and severe consequences for victim’s health conditions. The main objective was to examine risk factors and know mechanisms of slip-induced injuries associated with public swimming pools. A descriptive observational study of the Spanish population was conducted, using data from judicial sources from 2000 to 2015. In most cases, the common mechanism of the injury was a slip-induced fall at the same level (79.2%) originated while the subject was walking (65.6%) on a slippery floor (35.2%) with water (64.8%), being walkable area around a pool basin was the most cited location (19.2%). Slips are preventable and the effective application of international standards regarding slide-resistant surfaces could provide more reliable guarantee to protect the user health in swimming pools.